Terazosin Analogs Targeting Pgk1 as Neuroprotective Agents: Design, Synthesis, and Evaluation - Wang, Yang; Qian, Shihu; Zhao, Fang; Wang, Yujie; Li, Jiaming (Frontiers in Chemistry, 2022)
Nitrogen-containing heterocyclic compounds have shown promising therapeutic effects in a variety of inflammatory and neurodegenerative diseases. Recently, terazosin (TZ), a heterocyclic compound with a quinazoline core, was found to combine with phosphoglycerol kinase 1 (Pgk1) and protect neurons by enhancing Pgk1 activity and promoting glycolysis, thereby slowing, or preventing the neurodegeneration of PD. These findings indicated that terazosin analogs have bright prospects for the development of PD therapeutics. In this study, a series of terazosin analogs were designed and synthesized for neuroprotective effects by targeting Pgk1. Among them, compound 12b was obtained with the best Pgk1 agonistic activity and neuroprotective activity. Further study indicates that it can increase intracellular ATP content and reduce ROS levels by stimulating the activity of Pgk1, thereby playing a role in protecting nerve cells. In conclusion, this study provides a new strategy and reference for the development of neuroprotective drugs.